THE PHENOMENON OF “SIMULACRUM” IN THE WORKS OF TITUS LUCRETIUS CARUS - Mariia A. Oleshchenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. We are going to analyze the understanding of simulacra in the works of the ancient philosopher Titus Lucretius Carus, to determine the features of the phenomenon of "simulacrum" in his paper "On the Nature of Things". Results and discussion. The results of the study were that the simulacrum of Lucretius was complexity and diversity. It was illustrated by the author of article, that the poetic work "On the Nature of Things", not just a poetry, but also deep philosophy and naturalistic system. Scientific innovation. It was discovered that the understanding of the simulacrum of Lucretius is a little explored field. The basis work for this research was “Lucretius and naturalism” G. Deleuze. Conclusions. The principal conclusion was that creativity Titus Lucretius Carus usually perceived as a manifestation of the Roman poetic word or description of the nature of things in a metaphorical form. However, in this article was made investigation of Lucretia’s interpretation of the phenomenon of "simulacrum".